Framework for Secure Wireless Communication in Wireless Sensor Networks. (2nd December 2013) - Usama, Muhammad; Bin Muhaya, Fahad T.
Abstract : With large-scale and rapid development in wireless sensor networks (WSNs), there is great demand to adopt security mechanisms for secure wireless communication. WSNs have many fields of applications that are playing an essential role in increasing productivity and reducing cost. The restricted and constrained nature of sensors along with potentially dynamic behavior of WSNs demands the proper implementation of framework for secure communication in order to prevent attacker from illegally accessing or altering the transmission. We proposed a framework for secure wireless communication in WSNs which consists of four modules, that is, redundancy checker, message prioritization mechanism, malicious node verification, and malicious data verification. Detailed results of security and performance analysis have been realized for comparison and evaluation with complete implementation using NS2 network simulator. The proposed framework presents numerous interesting features which proofs acceptable performance for malicious node and data detection in WSNs.